Organ donation: The experience of health care professionals - Castelli, Isabela; Meneses, Nayanne da Ponte; Costa Junior, Áderson Luiz (Brazilian Journal of Transplantation, 2016)
Based on the regulation of the National Transplantation System upon the creation of the Intra Hospital Commission for Organ and Tissue Donation for Transplant (CIHDOTT) teams, a new field was structured for health professionals. Its main tasks are to organize the organ donation and transplantation process; to detect patients classified as potential donors and ask the family of the patient for their willingness for the organs donation for transplantation. Purpose: Having in mind that working in hospitals is a potentially stressful activity, and within the context described above aggravated by the direct contact with the death and finitude, a group of nine healthcare professionals from a public hospital in Bras lia was interviewed in order to understand their experience on the work. Method: The healthcare professionals were invited to participate in the present study, which was based on the semi-structured interview method. The interviews were audio recorded and fully transcribed. Subsequently, the analysis of the discourse was carried out with the elaboration of the thematic axes. Results: In the present text, we highlight the following categories: emotional charge, considerations on the death and focus on the recipient. Conclusion: The data discussed here, in accordance with the current literature emphasizes the need for an adequate training of the CIHDOTT healthcare teams, as well as the importance of spaces for hearing and peer exchanges.